Weight, height and BMI references in Elazi?: An east Anatolian city - Pirinçci, Edibe; Mümtaz Mazicio?lu, M.; Berbero?lu, Ufuk; Açik, Yasemin; Durmuş, Birsen; Öztürk, Ahmet (Turkish National Pediatric Society, 2011)
[Abstract Not Available]
Keywords: age determination; article; body height; body mass; body weight; child; child growth; controlled study; female; health care planning; human; male; preschool child; primary school; process monitoring; reference value; school child; sex difference; Turkey (republic)